Argentina : Detailed Assessment of Compliance of Basel Core Principles for Effective Banking Supervision. (IMF Staff Country Reports; Country Report ;, 2012)
This paper is a detailed assessment of compliance of the Basel Core Principles for effective banking supervision adopted by the Argentinean government. The financial sector in Argentina is dominated by the banking sector, with financial conglomerates managing about 85 percent of banking assets, 78 percent of investment funds, and 32 percent of insurance business. The Executive Board identifies the need for strengthening political and financial independence of the Central Bank of Argentina (BCRA). They also recommend a suitable legal framework for banking supervision and powers to enforce compliance with laws and regulations.